Secondary scintillation of He-CF4 mixtures with H-rich additives: contribution to the CYGNO Experiment - Roque, Rita Joana da Cruz (2023)
Tese de Doutoramento em Engenharia Física apresentada à Faculdade de Ciências e Tecnologia